A comparative study of benzalkonium chloride-free latanoprost versus benzalkonium chloride-preserved latanoprost on ocular surface health in patients of primary open angle glaucoma - Chhabra, Hema; Gupta, Anita; Singh, Gursatinder (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Prolonged use of anti-glaucoma therapy leads to development of ocular surface disease (OSD). The purpose of this study was to compare the effect of Benzalkonium chloride (BKC)-free latanoprost and Benzalkonium chloride (BKC)-preserved latanoprost on ocular surface health in patients of primary open angle glaucoma (POAG). Methods: This was a prospective, open-label, randomized, interventional, switch trial. 30 established cases of POAG who were already on BKC-preserved latanoprost for atleast more than three months were enrolled. Their Schirmer test and Tear film break-up time (TBUT) were recorded at the baseline. They were required to answer an ocular surface disease index (OSDI) questionnaire from which an OSDI score was calculated. They were switched to BKC-free latanoprost for another three months. On their follow-up visit at 6 weeks and 12 weeks, Schirmer test and Tear film break up time were performed again and OSDI score was calculated. Results: Schirmer test increased from 6.73±3.77 mm at baseline to 9.53±3.67 mm at 6 weeks and 11.97±3.53 mm at 12 weeks (p=0.001). Mean TBUT improved significantly from 6.77±3.82 seconds at baseline to 8.63±3.91 seconds at 6 weeks to 10.47±3.76 seconds at 12 weeks (p=0.001). OSDI score decreased from 31.55±23.32 at baseline to 23.42±21.93 at 6 weeks to 15.82±20.10 at 12 weeks (p=0.001). Conclusions: BKC-free latanoprost led to improvement in tear film status or ocular surface health of glaucoma patients as compared to BKC-preserved latanoprost.